Determination of Iron and Zinc Absorption by Local Isolates of Saccharomyces cerevisiae to Produce Iron and Zinc in Organic Form - Hasim Munawar; Eni Kusumaningtyas; Agus Leeman; David S. Silitonga; Darmono Darmono (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Iron (Fe) and Zinc (Zn) play important role in health both of live stock and human. Fe and Zn in organic form were claimed increasing their viabilities. They bind to certain amino acid formed as a product of microbial metabolism. The Amount Fe and Zn absorbed may indicated the Fe and Zn organic produced. The aim of the study is to determine the absorption of microelement of Fe and Zn by local isolates of Saccharomyces cerevisiae to produce Fe and Zn in organic forms. S. cerevisae BCC F0205, BCC F0206, and BCC F0214 were treated with Fe or Zn 10 ppm to obtain S. cerevisae which has the highest of total concentration of Fe and Zn. Selected isolate was then treated with Fe or Zn respectively 2.5, 5, 10 ppm and their combination. Fe and Zn absorbed by isolates were measured by Atomic Absorption Spectrophotometer (AAS). The results show that S. cerevisae BCC F0205, BCC F0206, and BCC F0214 treated with 10 ppm Fe or Zn contained total concentration of Fe respectively 1.57, 3.07, 2.24 ppm and total concentration of Zn respectively 2.34, 3.20, 3.13 ppm. Then, S. cerevisae BCC F0206 treated with 2.5, 5, 10 ppm Fe or Zn, absorbed Fe 1.45, 0.50, 0.94 ppm and Zn 0.73, 0.38, 0.53 ppm respectively. Furthermore, combination of Fe and Zn (2.5:2.5, 5:5, 10:10 ppm) produce absorption of Fe 3.10, 2.13, 3.67 ppm and Zn 0.11, 0.10, 0.28 ppm per gram S. cerevisae BCC F0206. Percentages of absorption by S. cerevisae are up to 100% for Fe and up to 47.20% for Zn. In conclusion, this study indicated that S. cerevisae BCC F0206 absorb Fe and Zn higher than BCC F0205 and BCC F0214 and there are antagonistic interactions found between Fe and Zn in this research.